Achieving Zero Waste: Circular Economy Strategies in Australian Higher Education - Olabode Ogunmakinde (Construction Economics and Building)
The circular economy concept, which aims to minimise waste and make the most of resources, has gained global traction as a sustainable alternative to the traditional linear economy. In recent years, Australian universities have increasingly adopted these principles to align with global sustainability goals to reduce environmental impact, enhance resource efficiency, and foster a culture of sustainability within their communities. This study examined the implementation of circular economy protocols in Australian universities to achieve zero waste and promote sustainable practices. Specifically, it assessed universities' commitment to circular economy strategies, waste reduction, resource optimisation, and the net-zero agenda. The research involved a systematic literature review of 70 sources from 2012-2022. Text mining techniques, including co-occurrence analysis, were applied to a secondary dataset to reveal the relationships between circular economy principles and universities, thereby enhancing our understanding of these connections. between circular economy principles and universities. Emergent themes centered around sustainability-oriented economic models like circular and sharing economies. The analysis underscored the importance of sustainability, collaboration, and locality in achieving waste minimisation goals. Significantly, there was an overlap between circular economy principles and the United Nations Sustainable Development Goals (SDGs). Universities showed a growing commitment to these goals through sustainable practices. Region-specific strategies, dynamic collaborations, and community engagement played key roles in waste minimisation. The adoption of sustainable economic models, including circular economy, was prominent. In conclusion, the study provides insights into universities' roles in waste reduction, resource optimisation, and supporting the transition to a net-zero, circular economy.